Historical overview of the National University of San Marcos - Saco Rodríguez, Oscar (1998)
By choosing Francisco Pizarro in 1533; the town of Jauja as the main city of its governorate, being there a place and house for the University; and the same providence was taken by the founder of the city of Lima in 1533. In the provincial chapter of the Order of Santo Domingo, held in Cusco in July 1548, Fray Tomas de San Martin stated the need to found a general study in Lima.